2014
DOI: 10.11120/beej.2014.00027
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students with Audio Feedback

Abstract: Students express widespread dissatisfaction with academic feedback. Teaching staff perceive a frequent lack of student engagement with written feedback, much of which goes uncollected or unread. Published evidence shows that audio feedback is highly acceptable to students but is underused. This paper explores methods to produce and deliver audio feedback to a range of students engaged in a variety of academic tasks with the aim of maximising student engagement while working towards a framework which could incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 13 publications
1
30
1
1
Order By: Relevance
“…Overall, the results of our study support conclusions reached in other studies with regard to the benefits to students of audio feedback, especially in terms of the personal nature of this approach to feedback, its clarity, and its suitability for conveying detailed responses (Brearley & Cullen, 2012;Cooper, 2008;Ice, Swan, Kupczynski, & Richardson, 2008;Merry & Orsmond, 2008;Rotheram, 2009). Audio feedback was generally popular with our students, as was also noted by Rotheram (2009) andCann (2014), and students reported that they had a fuller learning experience, also shown by Cavanaugh and Song (2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, the results of our study support conclusions reached in other studies with regard to the benefits to students of audio feedback, especially in terms of the personal nature of this approach to feedback, its clarity, and its suitability for conveying detailed responses (Brearley & Cullen, 2012;Cooper, 2008;Ice, Swan, Kupczynski, & Richardson, 2008;Merry & Orsmond, 2008;Rotheram, 2009). Audio feedback was generally popular with our students, as was also noted by Rotheram (2009) andCann (2014), and students reported that they had a fuller learning experience, also shown by Cavanaugh and Song (2014).…”
Section: Discussionsupporting
confidence: 89%
“…The scientific literacy assignment (SLA) for which audio feedback was implemented was part of the BIO152 course at UTM. This course is an appropriate site from which to expand our understanding of the utility of audio feedback in promoting student engagement as (a) it is a compulsory first year course for students in any Biology program at UTM, (b) it is a large class (821 students in 2014), thus involving more participants than most research on audio feedback, where the classes were never larger than 200 students and generally involved fewer than 50 participants (Cann, 2014;Still, 2006), and (c) it is neither an online course (Ice et al, 2007;Wood et al, 2011), nor a specifically ELL (English Language Learner) focused course (Johanson, 1999) the types of courses in which much of the prior research has been conducted. That said, BIO152 does have a large ELL population (approximately 50% of the class), thus the results of this research are relevant to work on ELL pedagogy as well.…”
Section: The Bio152 Coursementioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have been carried out on RAF, they were mostly conducted in class courses, in which it is not clear if revised versions of the learners' assignments were involved. Further, most studies were done in face-to-face class contexts, in which face-to-face dialogue with the supervisor can help to clarify RAF comments (Cavanaugh & Song, 2014;Stern & Solomon, 2006;Cann, 2014;Cavanaugh & Song, 2015;Chew, 2014;Eckhouse & Carroll, 2013). Overall in these cases, the impact of RAF on the learning process is unclear.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have found that most learners and supervisors have an overall positive attitude towards RAF [19][20][21][22][23]. The underlying reasons for this attitude given in these references include the following: (1) Audio feedback means more feedback; a supervisor can say a lot more in five minutes than they can write in the same amount of time.…”
Section: Raf In Literaturementioning
confidence: 99%